Towards a contextually appropriate framework to guide counseling of torture survivors in Sub-Saharan Africa - Higson-Smith, Craig; Eagle, Gillian (Torture Journal, 2018)
Introduction: If the right to rehabilitation is to become a meaningful reality for torture survivors in sub-Saharan Africa, it is necessary that counseling practice be responsive to the contextual and cultural demands of the region. Recent reviews of evidence-based practice with torture survivors are discussed with a focus on those approaches developed and/or tested with torture survivors in sub-Saharan Africa. Methods: The results of a mixed methods study of ongoing torture rehabilitation work are reported. This study incorporated a review of 85 case files of torture survivors treated at torture rehabilitation centers in three countries in sub-Saharan Africa, and in depth interviews with fifteen counsellors and fourteen clients at those same centers. Quantitative data are presented in tabular form supported by uni- and bi-variate statistical analyses as appropriate. Qualitative data are presented in terms of themes identified through emergent coding. Results and discussion: Help-seeking torture survivors in this region are a diverse and highly symptomatic group, often struggling to survive with their families in precarious circumstances and under ongoing threat. In addition to incorporating key aspects of existing evidence-based practice, counselors also use a range of psychosocial approaches to assist torture survivors to protect and support their families in the face of seemingly overwhelming life challenges. We propose that more systematic methodologies that facilitate the inclusion of the voicesof clients and clinicians in ongoing international debates relating to evidencebased practice with torture survivors will enhance the application of such practices in diverse contexts.